2010
DOI: 10.1007/s11136-010-9633-5
|View full text |Cite
|
Sign up to set email alerts
|

Accomplishment level and satisfaction with social participation of older adults: association with quality of life and best correlates

Abstract: Purpose-This study aimed to (1) explore whether quality of life (QOL) is more associated with satisfaction with social participation (SP) than with level of accomplishment in SP and (2) examine respective correlates of accomplishment level and satisfaction with SP.Methods-A cross-sectional design was used with a convenience sample of 155 older adults (mean age = 73.7; 60% women) having various levels of activity limitations. Accomplishment level and satisfaction with SP (dependent variables) were estimated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 63 publications
4
44
1
3
Order By: Relevance
“…This finding is in line with the results of previous studies reporting that patients who are unwilling to engage in social participation (e.g., participation in an experiment) tend to have worse social-related QOL [31,32]. Because a large portion of patients with lower SR dropped out of this study, the longitudinal change pattern of QOL in patients with lower SR at baseline may not be a quadratic trajectory.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is in line with the results of previous studies reporting that patients who are unwilling to engage in social participation (e.g., participation in an experiment) tend to have worse social-related QOL [31,32]. Because a large portion of patients with lower SR dropped out of this study, the longitudinal change pattern of QOL in patients with lower SR at baseline may not be a quadratic trajectory.…”
Section: Discussionsupporting
confidence: 91%
“…Second, a study of social participation among older adults with physical disabilities (Levasseur, Desrosiers, & Noreau, 2004) found that older adults with better selfreported health performed better and were more satisfied with their social participation. Another study of accomplishment level and satisfaction with social participation of older adults with various levels of activity limitations found that greater satisfaction with social participation was best explained by the following factors: activity level perceived as stable, better self-reported health and well-being, higher activity level, and more facilitators in "social support and attitudes" (Levasseur, Desrosiers, & Whiteneck, 2010). Furthermore, depressed mood in older adults with chronic disabling conditions is found to restrict both social and leisure participation (Cardol et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…L' intégration sociale des personnes dont les capacités cognitives sont diminuées est une priorité afin de promouvoir le maintien à domicile, la santé, la qualité de vie ainsi que l' intégration sociale. Pourtant, les interventions favorisant l' intégration sociale actuellement offertes à cette clientèle sont rares et les ressources ne sont pas utilisées de façon optimale (Levasseur, Desrosiers, & Whiteneck, 2010). En ce sens, l' accompagnement personnalisé en intégration communautaire (APIC) a été développé, testé et implanté avec succès dans une région métropolitaine du Québec auprès d' une clientèle adulte victime d' un traumatisme craniocérébral (TCC).…”
Section: Résumé De L'articleunclassified